2010
DOI: 10.1080/10426500902812415
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Quantitative Structural Relationship Studies of Electrochemical Properties of the Nanostructures ofCis-Unsaturated Thiocrown Ethers and Their Supramolecular Complexes [X-UT-Y][M@C82] (M˭Ce, Gd)

Avat (Arman) Taherpour

Abstract: The endohedral lanthanidofullerenes, an important type of organolanthanides, are stabilized by the delocalization of the negative charges on the cages of fullerenes. Since the discovery of these classes of carbon compounds and their unusual structures and properties of these molecules, many potential applications have been suggested. Unsaturated thiocrown ethers with cis-geometry are a group of crown ethers that, in light of the size of their cavities and their conformational restriction compared to a correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Among the successful TIs in these applications, it is worth noting the molecular connectivity indices (70,71), including the Randic index (79). In 1993 and 1997, the Wiener and Harary indices were applied to studies of fullerenes (85)(86)(87). The use of effective mathematical methods in making strong correlations between chemical properties and the indices have been reported (80)(81)(82)(83)(84)(85)(86)(87), which is an important area of development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the successful TIs in these applications, it is worth noting the molecular connectivity indices (70,71), including the Randic index (79). In 1993 and 1997, the Wiener and Harary indices were applied to studies of fullerenes (85)(86)(87). The use of effective mathematical methods in making strong correlations between chemical properties and the indices have been reported (80)(81)(82)(83)(84)(85)(86)(87), which is an important area of development.…”
mentioning
confidence: 99%
“…In 1993 and 1997, the Wiener and Harary indices were applied to studies of fullerenes (85)(86)(87). The use of effective mathematical methods in making strong correlations between chemical properties and the indices have been reported (80)(81)(82)(83)(84)(85)(86)(87), which is an important area of development. The ratio of the sum of the number of carbon atoms (n c ) to the number of sulfur atoms (n s ) to the product of these two numbers (m cs ) was a useful numerical and structural value in the studies reported here on the unsaturated thiocrown ethers 1-9.…”
mentioning
confidence: 99%
“…Effective mathematical methods must be employed to make good correlations between several properties of chemicals. Several applications of the indices have been reported [42][43][44][45][46][47][48][49][50][51][52][53]. The number of carbon atoms in the various fullerene structures was determined with these applications.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies in different areas have used topological indices [42][43][44][45][46][47][48][49][50]. Any extrapolation of results from one compound to other compounds must take into account considerations based on a QSAR study, which depends on how close the chemical properties are of the compounds in question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation